Factors affecting patients' drug purchasing preference for non-communicable diseases in Metro Manila - Moya, Dawn Isabelle A.; Aquino, Mark Angelo A.; Rios, Kirsten Denise S.
Introduction: Non-communicable diseases (NCDs) account for 74% of global deaths, with a significant burden in low- and middle-income countries, including the Philippines, where they are a leading cause of mortality. Due to their chronic nature, NCDs require long-term therapy, often leading to high healthcare costs. To ease this financial burden, the government enacted the Generics Act and the Cheaper Medicines Act to promote access to quality and affordable medicines. Despite implemented policies, the objective to promote and encourage the widespread use of generic drugs has yet to be fully realized. Patients still favor branded options due to concerns about effectiveness, quality, and safety of unbranded alternatives.